Nilai Etika dalam Tortor Hata Sopisik pada Masyarakat Batak Toba di Kabupaten Samosir - Simbolon, Sufrianty; Nugrahaningsih, Ruth Hertami Dyah (Gesture: Jurnal Seni Tari, 2025)
This research aims to describe the ethical values in Tortor Hata Sopisik among the Batak Toba community in Samosir Regency, using the ethical value theory according to K. Bertens who defines ethics as norms that regulate human behavior. This qualitative research was conducted at Sanggar Seni Sukacita, Ronggurnihuta, Samosir Regency, with a sample consisting of 6 Tortor Hata Sopisik dancers and 2 artists as informants. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively. The research results show that each type of movement in Tortor Hata Sopisik reflects ethical values based on religious norms, morality, politeness, and law. Religious norms are evident in the somba movement, which teaches prioritizing God and adhering to religious rules from an early age. The norms of decency are evident in the hushed movements that convey the heart's content subtly. The norm of politeness is reflected in the prohibition of excessive touching of the opposite sex, respecting women, and maintaining dignity. Legal norms are manifested through rules prohibiting dance partners from having the same clan or being in the dalihan na tolu kinship, in accordance with Batak customs that forbid marriage within the same clan.